Leaf anatomy of youngia japonica (l.) dc. (asteraceae) from Pahang, Malaysia - Abdul Rashid, Zainab Sholehah; Che Amri, Che Nurul Aini; Shahari, Rozilawati (Zibeline International Publishing, 2022)
Leaf anatomical and micromorphological studies on Youngia japonica (Asteraceae family) were accomplished. In the North America, this wild plant is consumed as salad as a healthy diet. The whole plant is edible and has been consumed in past years especially during famine. The Chinese community has been using this plant to perform blood cleansing, to cure sore throat, diarrhoea, mastitis, shingles, sprains, and bruises. Since there is yet any comprehensive study on the taxonomic study of Y. japonica in Kuantan, this study aims to investigate and examine its leaf anatomical and micromorphological characteristics that can be used as a complete guidance for its identification and additional data for its species classification. The methods involved in the leaf anatomy included a cross sectioning method on the petiole, midrib, lamina, and margin using a sliding microtome, clearing of venation using basic fuchsin, and epidermal peel methods using Jeffrey solution. The micromorphology of the leaf was observed under a scanning electron microscopy (SEM). The result of the characteristics of leaf anatomical and micromorphological studies for Y. japonica found the type of vascular bundle at petiole which was an opened system, noncontinuous ring of separated vascular bundle arranged in arc-shaped with additional vascular bundles, there were presence of mucilage cells, incomplete marginal venation, anomocytic stomata at leaf epidermis, granules and crust of wax, and multicellular trichomes with different ended and capitate glandular trichome. In conclusion, the findings have shown that the anatomical and micromorphological characteristics have their taxonomic value and can be useful in the identification, differentiation, and classification of the plant at the species level.